Three Economic-Social Systems and Freedom of Speech - Mickunas, Algis; Kacerauskas, Tomas (Transformations In Business & Economics, 2025)
The paper deals with the interconnection between economic wealth, the socio-economic system, and freedom of speech. The different socio-economic systems, including plutocracy, autocracy, and democracy, are investigated. Three theses are developed as follows. 1. Only democracy ensures both freedom of speech and economic well-being. 2. Plutocratic orientation toward wealth does not ensure social well-being if it does not play in concert with freedom of speech. 3. Despite promoting some philosophers (such as Plato), the aristocratic state order cannot ensure social well-being because of restrictions on freedom of speech and tends to totalitarianism. The methods of classification, comparison, and philosophical reflection are used. The findings are as follows. The comparison of three politico-economic systems shows interconnections between political order, freedom of speech and actions, and economic development. Although plutocracy is oriented toward economic profit and prosperity, it has no public arena for public issues in an open dialogue, and the economy works for the few winners. In autocracy, both political rights and freedom of speech are restricted. Only economic freedom is allowed if it does not contradict the ruler’s pronouncements. Finally, this system works again in economic prosperity. There is a correlation between democracy, freedom of speech, and well-being. Finally, this system leads to economic prosperity. However, democracy is inseparable from public debates and discussions that make society stronger and wiser.